2012
DOI: 10.4314/wsa.v35i1.76715
|View full text |Cite
|
Sign up to set email alerts
|

The use of hydrodynamic disintegration as a means to improve anaerobic digestion of activated sludge

Abstract: Disintegration by hydrodynamic cavitation has a positive effect on the degree and rate of sludge anaerobic digestion. By applying hydrodynamic disintegration the lysis of cells occurs in minutes instead of days. The intracellular and extracellular components are set free and are immediately available for biological degradation which leads to an improvement of the subsequent anaerobic process. Hydrodynamic disintegration of the activated sludge results in organic matter and a polymer transfer from the solid pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 8 publications
0
13
0
4
Order By: Relevance
“…The value of the reaction rate coeffi cient for the solubilisation of the solid waste fraction (hydrolysis) at 37°C calculated on the basis of designated parameters k 20 and θ amounts to 0.88 d -1 . For comparison, the values of the reaction rate coeffi cients k for the biochemical degradation reaction given in the literature amount to, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The value of the reaction rate coeffi cient for the solubilisation of the solid waste fraction (hydrolysis) at 37°C calculated on the basis of designated parameters k 20 and θ amounts to 0.88 d -1 . For comparison, the values of the reaction rate coeffi cients k for the biochemical degradation reaction given in the literature amount to, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The value of the coeffi cient θ which describes the temperature effect on the reaction rate is presented in the literature in the range between 1.013 (sewage sludge) and 1.066 (hydrocarbons) [3,20,21]. The higher the value of this coeffi cient, the higher the temperature effect on the decomposition rate, and thus the substrate biodegradability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, at low applied energy only floc disintegration is observed, while high energy is required to damage microbial cells (Appels et al, 2008;Carrère et al, 2010). Although not many results are available for mechanical pre-treatments in respect to the other methods, it is demonstrated that the efficiency of most of the technologies in improving AD of sewage sludge is rather low, if not coupled with other methods (Cho et al, 2014;Grübel and Machnicka, 2009;Kampas et al, 2007;Machnicka et al, 2009).…”
Section: Introductionmentioning
confidence: 94%
“…Pre-treatments can be grouped into biological, thermal, mechanical, chemical as well as different combination of these (Appels et al, 2008;Barjenbruch and Kopplow, 2003;Bougrier et al, 2006;Carrère et al, 2010;Kavitha et al, 2014;Kim et al, 2003;Nagare et al, 2008;. In the wide scenario of lysis technologies, mechanical and thermal pretreatments are the most common systems available on the market, working in full scale plants with good results in terms of COD solubilization and AD performance improvement (Bougrier et al, 2008;Choi et al, 2006;Climent et al, 2007;Dohányos et al, 1997Dohányos et al, , 2004Ferrer et al, 2008;Grübel and Machnicka, 2009;Kampas et al, 2007;Machnicka et al, 2009;Zábranská et al, 2006). Soluble COD (SCOD), that is the amount of COD in the liquid phase (after 0.45 lm filtration), is a parameter of easy analytic determination strictly related to sludge degradability.…”
Section: Introductionmentioning
confidence: 99%